Influence of strength and power capacity on change of direction speed and deficit in elite team-sport athletes - Freitas, T. T.; Pereira, L. A.; Alcaraz, P. E.; Arruda, A. F. S.; Guerriero, A.; Azevedo, P. H. S. M.; Loturco, I. (Journal of Human Kinetics, 2019)
The aim of the present study was to investigate the influence of maximum strength and power levels on change of direction (COD) ability and deficit in elite soccer and rugby players. Seventy-eight elite athletes (soccer, n = 46; rugby, n = 32) performed the following assessments: squat and countermovement jumps (SJ and CMJ), 1 repetition-maximum in the half-squat exercise (HS 1RM), peak power (PP) in the jump-squat exercise, and 20-m linear sprint and Zigzag COD tests. Utilizing the median split analysis, athletes were divided into two groups according to their HS 1RM and PP JS (e.g., higher and lower HS 1RM and higher and lower PP JS). The magnitude-based inference method was used to analyze the differences between groups in the physical performance tests. Athletes in the high strength and power groups outperformed their weaker and less powerful counterparts in all speed and power measurements (i.e., 5-, 10-, and 20-m sprint velocity, Zigzag COD speed, and CMJ and SJ height). In contrast, stronger and more powerful athletes displayed greater COD deficits. The present data indicate that players with superior strength-power capacity tend to be less efficient at changing direction, relative to maximum sprinting speed, despite being faster in linear trajectories. From these results, it appears that current strength and power training practices in team-sports are potentially not the "most appropriate" to increase the aptitude of a given athlete to efficiently utilize his/her neuromuscular abilities during COD maneuvers. Nevertheless, it remains unknown whether more multifaceted training programs are effective in decreasing COD deficits. Keywords: soccer; agility; sprint velocity; COD performance; cutting